Impact on Cluster Frontline Demonstrations on the Productivity of Mustard (Brassica juncea) - Balai, Laxman Prasad; Singh, Navab; Sharma, D. R. (International Journal of Bio-resource and Stress Management, 2021)
Cluster frontline demonstrations (CFLDs) are the long-term educational activity conducted in a logical method on partner farmer’s field to show the worth of new technology under micro farming. The present investigation was carried out during the Rabi season (October to March) of respective year 2016-17 to 2019-20 under the National Food Security Mission, Government of India. Four hundred thirteen CFLDs were conducted in 165.2 ha area with the farmers and scientists of KVK. The CFLDs were conducted at adopted fifteen villages of Dholpur district. Cultivation technology was applied under CFLDs included scientific intervention. The highest yield was obtained in demonstrated practices (DP) with an average of 2272.00 kg ha-1 as compared to farmer practice (FP) with an average of 1829.00 kg ha-1. Further, an average additional return (Rs. 16,063.6), effective gain (Rs. 14,335.8), net return (Rs. 64,512.1 ha-1) and benefit-cos ratio (3.49) were found in the DP as compared to farmer practice. An average occurrence of Alternaria blight, white rust, stem rot, aphid were recorded 27.44, 5.93 and 14.85 and 25.05, respectively showed in DP as compared to farmer practice. An average extension gap, technology gap and technology index between and was noted 443.0 kg ha-1, 234.75 kg ha-1 and 10.39%, respectively. The results indicate that the use of scientific intervention under CFLDs to increase the production and profitability of Mustard.